2016
DOI: 10.1515/jomb-2016-0014
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Carcinoembryonic and Carbohydrate Antigen 19-9 Related to Some Clinical, Endoscopic and Histological Colorectal Cancer Characteristics

Abstract: SummaryBackgroundColorectal cancer (CRC) is an important oncological and public health problem worldwide, including Serbia. Unfortunately, half of the patients are recognized in an advanced stage of the disease, therefore, early detection through specific tumor biomarkers, such as carcinoembryonic (CEA) and carbohydrate antigen 19-9 (CA 19-9), is the only way to cope with CRC expansion.MethodsOur cross-sectional study evaluated the influence of some clinical, endoscopic and histological characteristics of CRC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…The C-reactive protein predicts reduced survival in gastrointestinal cancer patients and is a well-recognized marker of inflammation (31). Increased CRP concentration has been shown to be a strong independent prognostic factor of CRC (32). In our study, the serum CRP level was significantly higher in CRC patients than control subjects, and it was higher with the advancing TNM classification.…”
Section: Discussionmentioning
confidence: 99%
“…The C-reactive protein predicts reduced survival in gastrointestinal cancer patients and is a well-recognized marker of inflammation (31). Increased CRP concentration has been shown to be a strong independent prognostic factor of CRC (32). In our study, the serum CRP level was significantly higher in CRC patients than control subjects, and it was higher with the advancing TNM classification.…”
Section: Discussionmentioning
confidence: 99%
“…All rights reserved This article is published online with Open Access and distributed under the terms of the Creative Commons Attribution Non-Commercial License (CC BY-NC 4.0). sitivity and specificity are different and not all patients have positive tumor markers available [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Further studies showed that it was also overexpressed in adenocarcinomas of varying origin including gastric, hepatic, lung, pancreatic, ovarian and prostate (17)(18)(19)(20)(21)(22)(23)(24). In colon cancer, the specificity and sensitivity of CEA has been shown to vary with advancing tumor stage, with specificity ranging between 37% and 86% in advanced disease, providing a useful means of monitoring disease (25)(26)(27). CEA may also be elevated in benign conditions such as inflammatory bowel disease, pancreatitis and in smokers, limiting its utility in early-stage cancer and in patients with such conditions (28-31).…”
Section: Discussionmentioning
confidence: 99%
“…As an adjunct to direct measurement of lesions, several tumor markers including carcinoembryonic antigen (CEA), cancer antigen 19-9 (CA19-9) and cancer antigen 125 (CA125) have obtained United States Food and Drug Administration (FDA) approval for the monitoring of various gastrointestinal and gynecologic malignancies. These tumor markers along with cancer antigen [27][28][29] used in the monitoring of breast cancer are proteins shed by cancer cells and are readily measured in the laboratory using antibodies.…”
mentioning
confidence: 99%